Amarinth develops scalable pump seal support system ATUs that are ideally suited to short lead-time contracts. Issue 5 (May 2019) - Atkinson, Simon
Abstract : UK-based Amarinth Ltd, which specialises in the design, application and manufacture of centrifugal pumps and associated equipment for use in the oil and gas, petrochemical, chemical, industrial and power-generating markets, has developed a scalable, configurable range of pump seal support system automatic top up units (ATUs). Here we briefly look at these systems which are designed and manufactured in house and can be completed to meet short lead-time contracts.